(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2026)
This work aims at acquiring deeper knowledge about solar system components including valuable materials as well as clearing viable ways towards extra solar systems. To achieve as much as possible the proposed objectives a viable Self-Sustaining Power Machine (SSPM), including an energy supply and propulsion paradigm shift is proposed. This system will replace the Nuclear Thermal Power and Nuclear Electric Propulsion Systems avoiding its inherent drawbacks, constraints and limitations. Therefore, this research addresses the need to firstly explore accessible celestial bodies within our solar system—planets, their moons and valuable accessible asteroids to utilize their resources. A primary challenge in this endeavor is ensuring a reliable energy supply. Consequently, this article proposes a disruptive change in both: energy supply and propulsion technology, replacing nuclear-based systems with SSPMs. These autonomous space vehicles would integrate the necessary SSPM-based resources to supply electrical power to all critical services and/or systems. Research results indicate us that the propellant fluid is crucial for achieving optimal results (high specific heat and low density with a high adiabatic expansion coefficient) ─(H₂). High temperature allows for high propellant expulsion velocity, resulting in high specific impulse and high thrust under lower propellant flow rate. Hydrogen (H₂) dramatically outperforms Nitrogen (N₂). At 3000K, H₂ achieves an exhaust velocity of 10.34 km/s (Isp 1054 s), while N₂ only reaches 2.74 km/s (Isp 280 s). H₂ produces significantly more thrust than N₂ under the same conditions. For example, at a mass flow rate of 100 kg/s and 3000K, H₂ generates 103.4 tons of thrust, while N₂ generates only 27.4 tons (Tables 17 & 20). With 50 tons of propellant to push a 10-ton spacecraft, H₂ heated to 3000K can achieve a final velocity of 26.5 km/s. N₂ under the same conditions can only reach 7.0 km/s, a massive difference in transit time and mission reach